Spiritual Ecology and Indigenous Wisdom: Cultural Foundations for Sustainable Environmental Practices in Indonesia - Yulisinta, Florence; Murniati, Juliana; Eigenstetter, Monika (UIN Sunan Gunung Djati Bandung, 2024)
This study explores the intersection between spiritual ecology and indigenous wisdom as foundational elements for sustainable environmental practices in Indonesia. The research aims to address the underexplored integration of cultural and spiritual values within modern environmental policies by demonstrating how traditional ecological knowledge and spiritual beliefs foster pro-environmental behaviour. Employing a qualitative phenomenological approach, data were collected through semi-structured interviews with four individuals actively engaged in conservation work across non-profit, indigenous, household, and educational sectors. Thematic analysis was used to identify key motivational patterns rooted in religious responsibility, spiritual reflection, gratitude for nature, and concern for future generations. The findings reveal that spiritual and indigenous values serve as intrinsic drivers of ecological behaviour, aligning with the Bio-Psycho-Social-Spiritual (BPSS) framework. These values are translated into practical conservation efforts, such as forest protection, biodiversity preservation, and environmental education. The study suggests that the incorporation of indigenous spirituality into environmental governance can produce culturally grounded, ethically robust sustainability models. The originality of this research lies in its empirical linkage between lived spiritual experiences and policy-oriented environmental practices, offering a transdisciplinary perspective that bridges scientific rationality with cultural relevance.